Association between university students’ two-staged health screening and student health care utilisation: register based observational study - Tuomas Koskela; Noora Seilo; Susanna Paldanius; Reija Autio; Kristina Kunttu; Minna Kaila (BMJ Open)
Objectives The aim of this study was to explore how university students’ participation in a two-staged health screening at the beginning of university studies associates with student health care utilisation in a 6-year follow-up.Design Nationwide, observational, register-based cohort study with a 6-year follow-up.Setting Student health care in Finland. Finnish Student Health Service (FSHS) provides statutory student health services to university students in Finland. The two-staged health screening of FSHS includes the electronic health questionnaire (eHQ) provided annually to university entrants and a subsequent health check, when necessary, based on students eHQ response.Participants A national cohort of university entrants from the 2011–2012 academic year (N=15 723) was assessed. After exclusions the study population consisted of 12 972 students, n (female)=7368, n (male)=5604.Outcome measures The primary outcome measures were students’ health service utilisation pattern obtained by clustering analyses method and the students’ participation in different stages of the health examination process.Results Four distinguishable health care utilisation patterns were identified: (1) constant low use, (2) constant high use, (3) increasing use and (4) decreasing use. The students’ OR for belonging to the constant high use group was significantly higher among females (OR 4.0, 95% CI 3.5 to 4.6) and students who attended the health check (OR 4.7, 95% CI 3.9 to 5.6).Conclusions Participating in the two-staged health screening was associated with increase in health care utilisation. The process detects students with health problems.